Application Management Project Based on Technology Information : Study Case ASANA Evaluation of Courses Interaction Humans and Computers Surabaya State University - Suroni, Azis; Sisephaputra, Bonda; Yahya, Saifudin (LPPM Institut Teknologi Telkom Purwokerto, 2025)
The development of information technology has had a significant impact on various sectors, including in the world of education, especially in project management. One of the popular information technology-based project management applications is ASANA, which offers various features to facilitate team collaboration and task management. This article aims to evaluate the use of ASANA in the Human Computer Interaction (HCI) course of the Informatics Undergraduate Study Program at Surabaya State University (UNESA) Campus 5, with a focus on ease of use, the effectiveness of team collaboration, and its impact on student work outcomes. This study uses a case study method by collecting data through questionnaires and interviews with students who use ASANA in group projects. The results of the study indicate that ASANA provides convenience in organizing tasks, speeding up communication between team members, and increasing transparency and accountability in project completion. However, several challenges such as difficulties in initial adaptation and limited features in the free version of ASANA were found in the use of this application. Overall, the ASANA application has proven effective in supporting project management in the HCI course, but there are several aspects that need to be improved to maximize its benefits. This study is expected to provide insight into the development of information technology-based project management methods in academic environments.